Mengapa Pancasila Mirip dengan Komunisme? Perspektif Guru Gembul - Latif Palikal Isbah Isbah; Ahmad Faisal (Journal of Information Systems and Management (JISMA), 2023)
- The purpose of this research is to find out Guru Gembul's perspective on the similarities that exist between communism and Pancasila. In this study report, a qualitative descriptive method was used by listening closely because the data source was obtained by listening to the oral narrative from Guru Gembul's YouTube channel entitled "Eps 625 Why is Pancasila Similar to Communism? Is Ms. Megawati aware?" which he explained. The result is that Pancasila and Communism are two fundamentally different ideologies. Pancasila is an ideology based on the noble values ​​of the Indonesian nation, which upholds the values ​​of humanity, unity, and social justice. Meanwhile, communism is an ideology based on historical materialism, which views history as a class struggle between the proletariat and the bourgeoisie. One of the fundamental differences between Pancasila and Communism is in terms of views on religion. Pancasila recognizes the existence of God Almighty, while communism views religion as an opium that hinders the progress of society. This difference is also reflected in the first principle of Pancasila, namely Belief in One Almighty God. This principle emphasizes that the Indonesian nation is a religious nation, which upholds divine values. Another fundamental difference between Pancasila and Communism is in terms of views on the state. Pancasila views the state as a tool to achieve common goals, while communism views the state as a tool to achieve a classless society. This difference is also reflected in the fourth principle of Pancasila, namely democracy led by wisdom in representative deliberations. This principle emphasizes that Indonesia is a democratic country led by the people and for the people. Pancasila is an ideology that is the basis for national and state life in Indonesia. Pancasila has been proven to be able to unite the Indonesian nation which is diverse and rich in differences. Meanwhile, communism is an ideology that is contrary to the values ​​of Pancasila and has been proven to cause a lot of suffering for people in various countries. Keywords: Communism, differences, ideology, Pancasila, Religion, state,